Mineral composition of melaphyre rocks and durablity of a motorway surface = Skład mineralny skał melafirowych a trwałość autostrady - Chrzan, Tadeusz; Zaworska, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the mineral composition of melaphyre and discusses durability of minerals contained in the rock for the impact of weather conditions on stability and strength of mineral rocks. The analysis showed that the tested melafir contained too many minerals not resistant to weathering.
Keywords: skała melaforowa; autostrada; nawierzchnia autostrad; warstwa wierzchnia; melaphyre rocks; motorway; surface layer